The Role of Strategic Partnerships and Digital Transformation in Enhancing Supply Chain Agility and Performance - Ibrahim Mutambik (Systems)
In times of disruption, a company’s ability to manage its supply chain effectively can determine its success or failure. This paper explores the extent to which strategic partnership development, mediated by digital transformation, enhances supply chain effectiveness during such periods. A mixed methods approach was used, involving surveys and interviews with professionals from the Saudi Arabian manufacturing sector. The study’s findings reveal that digital transformation and strategic partnerships work synergistically together to enhance supply chain resilience and effectiveness, resulting in improved operational agility and adaptability. Four key enablers of supply chain digital transformation were identified: inter-business coordination, leadership, technological culture, and recruitment management. These insights contribute significantly to our understanding of how businesses can build resilient supply chains in uncertain environments.